Tinjauan Tata Kelola Keamanan RME Berdasarkan Prinsip Keamanan PMK No. 24 Tahun 2022 di RSUD Dr. H. Soewondo Kendal - Kurniadi, Arif; Pratama Nugroho, Muhammad Rakha (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2025)
Electronic medical record (RME) has legal value and must be kept confidential. According to the Minister of Health Regulation (PMK No. 24 of 2022), the security principles of RME implementation must consider confidentiality, integrity, and availability. This study aims to analyze the implementation of RME security at RSUD Dr. H. Soewondo Kendal. It is qualitative and descriptive, using interviews with 10 medical record officers. The observation was carried out by observing the security practices of RME implementation. The results showed that there was a practice of exchanging passwords or using shared passwords. The principle of integrity has been carried out well by guaranteeing the completeness of RME, using digital signatures, a guidebook for writing abbreviations, and data corrections carried out no later than 2x24 hours from the time the data is entered. The principle of availability found discrepancies in determining the category of minors. The information release SOP states that minors are less than 14 years old, but PMK 24 states less than 18 years old. There is a need to increase understanding and discipline in the use of passwords for RME data security. It is necessary to adjust the SOP for the release of medical information at RSUD Dr. H. Soewondo Kendal by referring to the PMK No. 24 of 2022 guidelines